The analysis of suicide deaths in the Lublin macroregion in the years 2000–2010 - Skórzyńska, Hanna; Włoch, Małgorzata; Kulik, Teresa B.; Pacian, Anna; Krawczyk-Suszek, Marlena; Kaczoruk, Monika (Medical Studies/Studia Medyczne, 2016)
Introduction: Suicide is a serious social problem of global and national significance. Although Poland is a country with a relatively low suicide risk, it is the cause of death of several thousand people every year, roughly the same number as those who perish in road accidents. Aim of the research: To trace the number of suicidal deaths in the Lubelskie Region over a period of 11 years, and to analyse the breakdown of suicides and the tendencies of this phenomenon in the macroregion. Material and methods: The data were obtained with the permission of the Lublin Provincial Police Commander from the Lublin Provincial Police Headquarters. The data included the statistics of suicidal deaths from 2000 to 2010 in the Lublin Macroregion. Results and conclusions: Male sex is prevalent for suicides (86.4%) over female sex (14.6%). Suicides have most often concerned persons at the age of 30–50 (36.6%). Young people up to 20 take the fourth place in the age category (6.8%). The most exposed to risk of suicide are individuals with primary education (26.5%). The overall number of suicides in the Lubelskie Region has slightly risen in the past few years, although this differs by location within the macroregion. Increasing risk of suicide is a challenge for the prevention of the phenomenon, which should take suicidal risk factors into consideration. The most common cause of suicide It was a mental illness (15.1%). Family problems were the second cause of suicide. Economic problems were the cause of an average 5.1% of all suicides.